ANALISIS KEPUASAN KONSUMEN TERHADAP PRODUK SAMBAL KEMASAN UNTUK FORMULASI PERBAIKAN STRATEGI PRODUK - Rahayu, Fitriani; Barkah, Cecep; Chan, Arianis; Tresna, Pratami Wulan (BISMA: Jurnal Bisnis dan Manajemen, 2021)
Consumers have a high level of satisfaction with the quality of taste, flavour variants, packaging quality, price, and service quality of Sambel Gendang, while consumers have a low level of satisfaction with the level of spiciness of the product. This study aims to investigate the level of consumer satisfaction and formulate product strategy improvements to be proposed by considering customer satisfaction. Therefore, consumers can repurchase the products and become Sambel Gendang customers. This research uses descriptive analysis research with a quantitative approach. The population of this study was Sambel Gendang consumers. A total of 60 people were taken as samples by using probability sampling technique, and simple random sampling method. The results of this study revealed that 43.3% of respondents were satisfied with the taste quality, 41.7% were dissatisfied with the level of spiciness, 35% were satisfied with the flavour variant, 53.3% were satisfied with the packaging, 41.7% were satisfied with the price, 46.7% were satisfied with the service quality. The proposed marketing strategy by considering customer satisfaction is focused on product and promotion strategies to increase the sales market. Keywords: business, customer satisfaction, product, marketing strategies.